2010
DOI: 10.1007/s11355-010-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of river alteration for flood control on freshwater turtle populations

Abstract: The impacts of artificial river alteration for flood control on the dynamics of freshwater turtle populations were studied in small urban and rural river systems in northwestern Chiba Prefecture Low turtle population densities in other river sections where flood control measures have already been implemented suggest slow population recovery. River alteration practices also altered the age structures, sex ratios, and demographic characteristics of the turtle populations, although the exact consequences for popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…River turtles may have poorer body condition when flows are lower or less frequent because of reduced food supply and opportunities for foraging (Bondi & Marks, ; Howard, Beesley, Ward, & Stokeld, ). However, high river flows or velocities can also impair turtle populations (Lenhart, Naber, & Nieber, ; Usuda, Morita, & Hasegawa, ). Although flows in the Bellinger River were sometimes low in spring 2014, the river did not cease to flow or fall below historical low flows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…River turtles may have poorer body condition when flows are lower or less frequent because of reduced food supply and opportunities for foraging (Bondi & Marks, ; Howard, Beesley, Ward, & Stokeld, ). However, high river flows or velocities can also impair turtle populations (Lenhart, Naber, & Nieber, ; Usuda, Morita, & Hasegawa, ). Although flows in the Bellinger River were sometimes low in spring 2014, the river did not cease to flow or fall below historical low flows.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures are usually beneficial to freshwater turtles, because warmer waters tend to have greater food productivity, or allow a longer growing season and more rapid food digestion (Ashton, Bettaso, & Welsh, 2015;Frazer, Greene, & Gibbons, 1993;Gibbons, 1970;Thornhill, 1982 (Bondi & Marks, 2013;Howard, Beesley, Ward, & Stokeld, 2016). However, high river flows or velocities can also impair turtle populations (Lenhart, Naber, & Nieber, 2013;Usuda, Morita, & Hasegawa, 2012). Although flows in the Bellinger River were sometimes low in spring 2014, the river did not cease to flow or fall below historical low flows.…”
Section: Growthmentioning
confidence: 99%
“…Therefore, temperature ultimately determines the distribution and population dynamics of freshwater turtles. Furthermore, micro-habitat environments, such as current velocity (e.g., Buhlmann and Vaughan, 1991;Usuda et al, 2012;Kagayama, 2019), may also be important. For example, Kagayama (2019) surveyed the distribution patterns of three freshwater turtle species in the Yorogawa River system (35°24'2.5842" N, 140°7'46.6896" E) and showed that M. reevesii and T. s. elegans were abundant in the lower regions of the river, whereas M. japonica was abundant in the middle and upper regions of the river.…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that climatic factors, such as the highest temperature of the warmest month (August), the lowest temperature of the coldest month (January), and total daylight hours limited the distribution of freshwater turtle species because these ectotherms required moderate temperatures and solar radiation to control their body temperature (Vitt and Caldwell, 2014). Furthermore, slope as the topographic factor and precipitation may affect the dispersal or establishment of freshwater turtles in the high-elevation regions because the distribution of turtles may be limited by the velocity of water currents (Buhlmann and Vaughan, 1991;Usuda et al, 2012;Kagayama, 2019). All five variables of grid data were divided by 1 km grid cells using ArcGIS 10.0 (ESRI, CA, USA), and we calculated only the total daylight hours from April to November using ArcGIS 10.0 and the Mesh Climate Value, which is a contiguous nationwide grid consisting of 1 km 2 cells because most freshwater turtles hibernate during winter in the water (Ultsch, 1989).…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation